Influence of multi-dimensional environmental knowledge on residents' waste sorting intention: Moderating effect of environmental concern - He, Zhihua; Liu, Yong; Liu, Xiaochun; Wang, Feng; Zhu, Huijia (Frontiers in Psychology, 2022)
With the rapid increase in household waste, environmental degradation becomes more serious. It is imperative to promote waste sorting in China. This study proposes an extended KAB model to explore the impact mechanism of different dimensions of subjective environmental knowledge on urban residents' waste sorting intention. The study also explores the moderating role of environmental concern in the relationship between three types of subjective environmental knowledge and attitude toward waste sorting. Based on 308 valid questionnaires, through structural equation model, multiple regression analysis, and simple slope test, we found that system knowledge, action-related knowledge, and effectiveness knowledge all have positive impacts on residents' attitudes toward waste sorting, and effectiveness knowledge has the most significant impact. Meanwhile, environmental concern positively moderates the relationship between system knowledge, effectiveness knowledge, and attitude toward waste sorting. This study makes an important theoretical contribution to enrich the existing literature on residents' waste sorting behavior and provides theoretical insights for governmental waste sorting policy formulation at the practical level.